Establishment of a simplified score for predicting risk during intrahospital transport of critical patients: A prospective cohort study - An, Ying; Tian, Zi‐Rong; Li, Fei; Lu, Qi; Guan, Ya‐Mei; Ma, Zi‐Feng; Lu, Zhen‐Hui; Wang, Ai‐Ping; Li, Yue (Journal of clinical nursing, 2023)
Aims and objectives To establish a simple score that enables nurses to quickly, conveniently and accurately identify patients whose condition may change during intrahospital transport. Background Critically ill patients may experience various complications during intrahospital transport; therefore, it is important to predict their risk before they leave the emergency department. The existing scoring systems were not developed for this population. Design A prospective cohort study. Methods This study used convenience sampling and continuous enrolment from 1 January, 2019, to 30 June, 2021, and 584 critically ill patients were included. The collected data included vital signs and any condition change during transfer. The STROBE checklist was used. Results The median age of the modelling group was 74 (62, 83) years; 93 (19.7%) patients were included in the changed group, and 379 (80.3%) were included in the stable group. The five independent model variables (respiration, pulse, oxygen saturation, systolic pressure and consciousness) were statistically significant (p < .05). The above model was simplified based on beta coefficient values, and each variable was assigned 1 point, for a total score of 0–5 points. The AUC of the simplified score in the modelling group was 0.724 (95% CI: 0.682–0.764); the AUC of the simplified score in the validation group (112 patients) was 0.657 (95% CI: 0.566–0.741). Conclusions This study preliminarily established a simplified scoring system for the prediction of risk during intrahospital transport from the emergency department to the intensive care unit. It provides emergency nursing staff with a simple assessment tool to quickly, conveniently and accurately identify a patient's transport risk. Relevance to clinical practice This study suggested the importance of strengthening the evaluation of the status of critical patients before intrahospital transport, and a simple score was formed to guide emergency department nurses in evaluating patients.